Utilizing Sandy AI to Enhance English Language Teachers’ Speaking Instructional Skills In MGMP Madrasah Aliyah Under The Ministry of Religious in Soppeng Regency - Guntur Bratama; Arqam Arqam; Magdahalena Tjalla; Zulfah Zulfah; Ambo Dalle (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
The integration of artificial intelligence (AI) in language education offers a promising pathway to enhance teacher competence, particularly in speaking instruction. Despite its potential, some English teachers in the MGMP (Musyawarah Guru Mata Pelajaran) Madrasah Aliyah under the Ministry of Religious Affairs in Soppeng Regency continue to face difficulties in effectively utilizing AI tools and delivering CEFR B1-level speaking materials, particularly expressions of suggestion and offering help. This study aimed to analyze the effectiveness of Sandy AI in improving teachers’ speaking instructional skills and to explore the integration of AI within professional development programs. Employing a Classroom Action Research (CAR) design using the Kemmis and McTaggart model, the research was conducted over two cycles and involved ten English teachers. Each cycle followed the stages of planning, acting, observing, and reflecting. In Cycle 1, teachers received initial training on Sandy AI and lesson development using the Problem-Based Learning (PBL) method. Following the first cycle, additional interventions were implemented in Cycle 2, including targeted CEFR B1 training, peer mentoring by high-performing teachers, and workshops on AI troubleshooting. Data collection was conducted through structured observation using a rubric that assessed instructional clarity, AI usage, CEFR explanation, and student engagement. The results demonstrated significant improvement in teacher performance, with a 32% increase in average scores and 90% of participants achieving the success criteria by Cycle 2. Teachers showed enhanced confidence, clearer instructional delivery, and more interactive use of Sandy AI in the classroom. The findings indicate that Sandy AI is an effective and practical tool to improve speaking instruction when supported by a structured, iterative professional development framework. This model is particularly applicable to religious-based educational contexts seeking to modernize language teaching through AI integration.